(untitled) (Global Journal of Medical Research, 2017)
Morus alba was broadly used with a long history of traditional medicinal remedy for the regimen of various illnesses. The current investigation was designed to evaluate anti-stress activity of aqueous and ethanol extracts of Morus alba. Anti-stress of aqueous and ethanol extracts of Morus alba was estimated by inducing stress in rats through the forceful swimming. Homovanillic acid (HVA), urinary vanillymandelic acid (VMA), 6-β-OH-cortisol, 5-hydroxyindoleacetic acid (5HIAA) and ascorbic acid were reckoned as non-invasive biomarkers to assess the adaptogenic activity. Daily oral administration of aqueous and ethanol extracts of Morus alba at dose of 200 and 400 mg/kg body weight one hour before the induction of stress to retard stress-induced urinary biochemical changes in a dose dependent manner. However, non-significant changes in the urinary excretion of Homovanillic acid (HVA), urinary vanillymandelic acid (VMA), 6-β-OH-cortisol, 5-hydroxyindoleacetic acid (5HIAA) and ascorbic acid was perceived when compared to basal levels in normal animals.